Price effects of minimum wages: Evidence from the construction sector in East and West Germany - Thomas Werner; Friedrich L. Sell; David C. Reinisch (Universität der Bundeswehr München, Fachgruppe für Volkswirtschaftslehre, 2013)
In this paper, the authors present a new approach to estimate the impact of a minimum wage on the labor market of the construction sector in Germany. Instead of estimating the effect on employment, the authors focus on the change of prices on a firm level in order to differentiate between a competitive and a monopsonistic structured labor market. The composition of the sector-specific labor market serves again as a basis to evaluate whether the consequences of the minimum wage can be taken as economically advantageous or disadvantageous. Using firm data monthly conducted by the Ifo Institute for Economic Research, the estimations show that the minimum wage did have a different impact in East and West Germany. In East Germany, we find significant positive price effects of the minimum wage which exclude the possibility of positive employment effects due to monopsonistic structures. On the contrary, our results indicate a competitive sectorspecific labor market and declining employment. In contrast, there was no significant price reaction observed for West Germany. The minimum wage seems too low compared to the wages paid in the West German construction sector. Therefore, the introduction of the minimum wage cannot be assumed to be binding.
Keywords: J08; J38; J42; J48; 330; labor market; minimum wage; employment effects; construction industry; difference-in-differences